MORPHOMETRIC PARAMETERS OF THE SPLEEN IN THE EARLY ANTENATAL PERIOD OF DEVELOPMENT - Zayniddinov Ogʻabek Farxod oʻgʻli; Oʻrazdurdiyeva Muqaddas; Egamberganova Mohimjon Mahmudjon qizi; Ikromova Shahlo Anvarovna Pediatrics, Group 204; Muxammadjonov Lochinbek (TADQIQOTLAR, 2026)
Abstract. In the study of spleen specimens from embryos and fetuses, at the 5th– 6th week a primary splenic rudiment was identified within the dorsal mesogastrium. By weeks 8–9, distinct red and white pulp precursors became recognizable, with early lymphocyte populations appearing in the periarteriolar sheaths. By weeks 11–12, the spleen demonstrated well-formed trabecular framework, sinusoidal vasculature, and primary lymphoid follicles. Two peaks of active lymphocyte proliferation were established: at 18–20 weeks and at 27–28 weeks of embryogenesis, coinciding with intensification of extramedullary hematopoiesis and expansion of the white pulp compartment.